Development of dentists perceptions and knowledge of teledentistry - Boanjoy, Sarah Margareth; Setiawan, Asty Samiaty; Suryanti, Netty (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
Teledentistry is a dental health service that provides consultation, guidance, or education remotely using information technology. Perception and knowledge play an essential role in the implementation of teledentistry. The purpose of this study was to explore the development of dentists' perceptions and knowledge of the concept of teledentistry. This study used a scoping review method based on the Joanna Briggs Institute methodology. Screening and study selection were carried out using the Preferred Reporting Items of Systematic Reviews and Meta-Analysis Scoping Reviews (PRISMA-Scr). Literature searches were conducted through PubMed, Science Direct, and EBSCOHost with keywords and inclusion criteria, hand searching, and viewing the list of selected article references. There were 23 articles analyzed according to the inclusion and exclusion criteria. Changes in dentists' perceptions of teledentistry would help shorten waiting list, reduce costs for dental practice, additional visits to take photographs, and additional costs to provide facilities/ equipment for teledentistry before and during the COVID-19 pandemic. Three articles (2015-2016) state that most dentists did not know or have little knowledge about teledentistry. Nine articles published during the pandemic revealed that the majority of dentists had knowledge of teledentistry. The results of this study found that developments in dentists’ perception, namely teledentistry would help shorten waiting list, reduce costs for dental practice, the need for additional visits to take photographs, and additional costs to provide facilities/ equipment for teledentistry. The level of knowledge of dentists about teledentistry increased during the COVID-19 pandemic.